SISTEM PAKAR DIAGNOSA PENYAKIT PADA KEHAMILAN MENGGUNAKAN METODE CERTAINTY FACTOR - Ari Ramadhan; Heti Mulyani; Kevin Perdana (JURTIK:Jurnal Penelitian dan Pengembangan Teknologi Informasi dan Komunikasi, 2019)
In pregnancy, there are many symptoms or diseases that can endanger the life of the mother and baby. This can happen due to a lack of information and socialization about diseases that can occur. So that this disease is only known when it is severe. Therefore, the author analyzes and designs an expert system for diagnosing diseases in pregnancy with certainty factor methods. The expert system for diagnosing diseases in pregnancy using the certainty factor method is an expert system designed as a tool to diagnose diseases in pregnancy that commonly occur in pregnant women with a dynamic knowledge base. In the application of this expert system is assisted by certainty factor methods. The certainty factor method has characteristics that match the way of thinking of an expert, but uses mathematical calculations based on the measure of belief and measure of disbelief, namely the concept of belief and the concept of unbelief. This method calculates through the symptoms selected by the user where each symptom has a confidence value obtained from an expert. This expert system was built using the Java Netbeans IDE 7.3.1 language and MySQL as the database. The methodology used for the development of this expert system is the waterfall methodology. From the design results, an expert system is obtained which contains information on common diseases that often attack pregnant women and how to handle them. With this expert system, it is hoped that it can assist pregnant women in diagnosing the type of disease in pregnancy by choosing specific symptoms and appropriate handling methods.